Durable acetylated rattan and method of preparation thereof - Hamid, Norul Hisham (2013)
The present invention relates to durable acetylated rattan for functional use such as outdoor building materials for house such as fencing, window frame, parquet flooring, column and beam. The present invention also relates to a method of preparation of durable acetylated rattan.